Osteolytic bone lesions in patients with primary myelofibrosis: A systematic review - Battukh, Naim; Ali, Elrazi; Yassin, Mohamed (Acta Biomedica Atenei Parmensis, 2022)
Philadelphia negative myeloproliferative neoplasms (MPNs) are classically characterized by excess production of terminal myeloid cells in the peripheral blood. They include polycythemia vera, essential thrombocythemia, and primary myelofibrosis. Among this group, primary myelofibrosis is the least common and usually carries the worst prognosis. Bone involvement in primary myelofibrosis has many forms; it affects bone marrow leading to bone marrow fibrosis, it can cause periostitis, in addition to bone and joint pain. A common radiologic finding in primary myelofibrosis is the presence of osteosclerotic lesions. However, the presence of osteolytic lesions in bone imaging was described in few reports. In this review, we searched English literature using the PRISMA guidelines looking for patients with Primary myelofibrosis who had osteolytic bone lesions to assess the impact of such findings on the disease and its effect on prognosis. We found the vast majority of lesions were painful affecting most commonly the vertebral column, pelvis, and ribs, and were detected in patients above 50 years of age with no gender preference, unfortunately they represented advanced disease stages, resulting in inadequate treatment response and poor outcome.